The quality of COPD care in German general practice—A cross-sectional study - Heinmüller, Stefan; Schaubroeck, Emmily; Frank, Luca; Höfle, Anina; Höfle, Anina; Langer, Michael; Saggau, Korbinian; Schedlbauer, Angela; Kühlein, Thomas (Chronic Respiratory Disease, 2020)
Objectives: Chronic Obstructive Pulmonary Disease (COPD) is a common health problem to be dealt with in primary care. Little is known about the quality of care provided for patients with COPD in Germany. Therefore, we wanted to assess the current quality of care delivered by a primary care network (PCN) for patients with COPD. Methods: A cross-sectional study was conducted in collaboration with a primary care network (PCN). All patients of the PCN aged 40 years and older with a diagnosis of COPD were identified through electronic health records (EHR). A set of quality indicators (QIs) developed in accordance with current COPD-guidelines were appraised through numerical data retrieved from the EHR. Results: In total, 2,568 patients with COPD were identified. Their mean age was 67 (SD±12) years, 49% were male. Thirty-five percent had a parallel diagnosis of asthma. There was no documentation of any spirometry for 54% of patients; 29% had a spirometry within the previous year. An influenza vaccination was documented for 37% within the preceding 12 months; 12% received a pneumococcal vaccination in the last 6 years. Smoking status was documented for 44% within the last year. Conclusion: The quality of care for patients with COPD in the PCN seemed suboptimal, despite the presence of a Disease Management Program (DMP). This finding is likely to apply widely to German general practice. Quality assessment through currently available EHR data was challenging due to non-standardized and insufficient documentation.
CRIS-Team Scopus Importer:2020-12-11
Keywords: chronic obstructive; documentation; general practice; practice guideline; Pulmonary disease; quality of health care